2011
DOI: 10.1002/jrs.3115
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in linear and nonlinear Raman spectroscopy. Part V

Abstract: as reviewed here, reflect trends at the cutting edge of Raman spectroscopy, which is expanding rapidly as a sensitive photonic probe of matter at the molecular level with an ever-widening sphere of novel applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 277 publications
1
32
0
Order By: Relevance
“…[1] SERS method applies locally enhanced electromagnetic field from metallic nanostructure to dramatically amplify Raman scattering, which has "fingerprint" unique to analytes but low cross-section compared to fluorescence method. [2] It was reported that the cross section for Raman is on the order of 10 -29 cm 2 sr -1 while that for fluorescence is 10 -16 cm 2 sr -1 . [3] Our laboratory demonstrated the first analytical application of SERS in chemical analysis by using metallic nanosubstrate and has been working on various nanoplatforms with different shapes and structures for SERS detection.…”
Section: Introductionmentioning
confidence: 98%
“…[1] SERS method applies locally enhanced electromagnetic field from metallic nanostructure to dramatically amplify Raman scattering, which has "fingerprint" unique to analytes but low cross-section compared to fluorescence method. [2] It was reported that the cross section for Raman is on the order of 10 -29 cm 2 sr -1 while that for fluorescence is 10 -16 cm 2 sr -1 . [3] Our laboratory demonstrated the first analytical application of SERS in chemical analysis by using metallic nanosubstrate and has been working on various nanoplatforms with different shapes and structures for SERS detection.…”
Section: Introductionmentioning
confidence: 98%
“…A perspective review of the field of Raman spectroscopy is published annually in the Journal of Raman Spectroscopy (JRS), first initiated in 2007 and continued through 2018 in which highlights of current trends in Raman spectroscopy are presented. The 2019 review incudes coverage of papers published in the JRS during calendar year 2018 as well as a survey of Raman topics included in conference programs this year at (a) the Tenth International Conference on Advanced Vibrational Spectroscopy (ICAVS 10) in Aukland, New Zealand in July; (b) SCIX 2019 organized by the Federation of Analytical Chemistry and Spectroscopy Societies (FACSS) in Palm Springs, California USA in October; (c) the European Conference on Nonlinear Optical Spectroscopy (ECONOS 2019) in Rouen, France in April; and (d) the Tenth International Congress on the Application of Raman Spectroscopy in Art and Archaeology (RAA 2019) in Potsdam, Germany in September.…”
Section: Introductionmentioning
confidence: 99%
“…Each year a perspective review of the field of Raman spectroscopy is published here in the Journal of Raman Spectroscopy ( JRS ) that was first initiated in 2007 and has been continued through 2016 in which highlights of current trends in Raman spectroscopy are presented. The scope of the present review includes papers published in the JRS during the 2016 calendar year as well as a survey of Raman topics included in the conference programs this year at (a) the XXV The Ninth International Conference Advanced Vibrational Spectroscopy (ICAVS‐2017) in Victoria, British Columbia, Canada, in June; (b) SCIX 2017 (Science Exchange), sponsored by the Federation of Analytical Chemistry and Spectroscopy Societies (FACSS), in Reno, Nevada, USA, in early October; (c) ECONOS 2017 in Jena, Germany, in April; and (d) The Ninth International Symposium on the Application of Raman in Art and Archaeology (RAA 2017) in Evora, Portugal, near the end of October.…”
Section: Introductionmentioning
confidence: 99%